دور أفراد المنظمات السياحية في توظيف المزيج التسويقي الإلكتروني -دراسة ميدانية (Journal of Economics and Management Research, 2021)
تهدف الدراسة الحالية إلى توضيح دور خصائص عينة الدراسة في استخدام الوكالات السياحية لأبعاد المزيج التسويقي الالكتروني السياحي. وقد انتهجت الدراسة المنهج الوصفي التحليلي على عينة من العاملين في وكالات السفر والسياحة المستقصاة مستخدمين 31 استبانة، وتم توظيف الأدوات الإحصائية المناسبة للدراسة واختبار فرضياتها. ووجدنا أن هذه الوكالات تهتم كثيرا باستخدام صفحات القايسبوك بالدرجة الأولى بينما القليل منها من يتبنى ويوظف كل عناصر المزيج التسويقي السياحي، كما سجلنا غياب دور السمات الشخصية للعينة في هذا التبني من عدمه. The present study aims to clarify the role of the characteristics of the study sample in the tourism agencies' use of the dimensions of the electronic tourism marketing mix. The study adopted a descriptive and analytical approach on a sample of workers in the travel and tourism agencies surveyed using 31 questionnaires. Appropriate statistical tools were employed for the study and testing its hypotheses. And we found that these agencies are very interested in using Facebook pages in the first place, while few of them adopt and employ all the elements of the tourism marketing mix, and we have noted the absence of the role of the personal characteristics of the sample in this adoption or not.